2016
DOI: 10.1007/s10865-016-9720-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Sensory Hypersensitivity Scale (SHS): a self-report tool for assessing sensitivity to sensory stimuli

Abstract: Sensory hypersensitivity is one manifestation of the central sensitization that may underlie conditions such as fibromyalgia and chronic fatigue syndrome. We conducted five studies designed to develop and validate the Sensory Hypersensitive Scale (SHS); a 25-item self-report measure of sensory hypersensitivity. The SHS assesses both general sensitivity and modality-specific sensitivity (e.g. touch, taste, and hearing). 1202 participants (157 individuals with chronic pain) completed the SHS, which demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 53 publications
0
50
0
Order By: Relevance
“…Questionnaires included the Fibromyalgia 2011 Diagnostic Criteria for WPI and SS scores, the Sensory Hypersensitivity Scale (SHS) , the Patient‐Reported Outcomes Measurement Information System (PROMIS) fatigue measure , and the Short Form Brief Pain Inventory measure (BPI) . Quantitative sensory testing (QST) was conducted immediately after MRI scanning and assessed pressure pain thresholds, mechanical hyperalgesia, mechanical temporal summation, and response to a cold pressor test (see Supplementary Methods, available at http://onlinelibrary.wiley.com/doi/10.1002/art.40746/abstract).…”
Section: Methodsmentioning
confidence: 99%
“…Questionnaires included the Fibromyalgia 2011 Diagnostic Criteria for WPI and SS scores, the Sensory Hypersensitivity Scale (SHS) , the Patient‐Reported Outcomes Measurement Information System (PROMIS) fatigue measure , and the Short Form Brief Pain Inventory measure (BPI) . Quantitative sensory testing (QST) was conducted immediately after MRI scanning and assessed pressure pain thresholds, mechanical hyperalgesia, mechanical temporal summation, and response to a cold pressor test (see Supplementary Methods, available at http://onlinelibrary.wiley.com/doi/10.1002/art.40746/abstract).…”
Section: Methodsmentioning
confidence: 99%
“…One such measure is the Sensory Hypersensitivity Scale (SHS)(Dixon et al, 2016). The SHS is a 25-item measure that assesses both general hypersensitivity as well as modality-specific sensitivity (e.g., touch taste, auditory).…”
Section: Chronic Overlapping Pain Conditions (Copcs): the Diagnosmentioning
confidence: 99%
“…Quantitative sensory testing may not be feasible in all clinical settings, so self-reported sensory hypersensitivity may also be used to document this phenomena. One such measure is the Sensory Hypersensitivity Scale (SHS; Dixon et al, 2016). The SHS is a 25-item measure that assesses both general hypersensitivity as well as modalityspecific sensitivity (e.g., touch taste, auditory).…”
Section: Generalized Sensory Hypersensitivitymentioning
confidence: 99%
“…For example, prior studies report mixed findings on the relationships between thermal pain sensitivity and non-noxious sensory sensitivity. 11,13,21 However, if MSS is related to chronic pain due to underlying shared central mechanisms as previously suggested, 11,12,14 then one might expect MSS to be more closely related to dynamic QST and referred pain, both associated with central mechanisms, [5][6][7]22 than to static QST or local pain. Unfortunately, studies are lacking that consider multiple QST modalities (eg, thermal and mechanical) using both static (thresholds) and dynamic (temporal summation or conditioned pain modulation) assessments or controlled experimentally induced pain models.…”
Section: Introductionmentioning
confidence: 90%
“…6,7 Emerging evidence suggests multisensory sensitivity (MSS) could potentially serve as an additional marker to reflect the status of CNS sensitivity as elevated MSS has been theorized to be attributable to a sensitized CNS. [11][12][13][14] Indeed, a review showed pre-morbid assessments of high sensory sensitivity using QST were predictors of central sensitization. 14 Several pain populations, suspected to involve central mechanisms or nociplastic pain, report hypersensitivity to normal daily sensations, such as light touch, bright light or noise.…”
Section: Introductionmentioning
confidence: 99%